Demokratyczny Islam. Koniec modernizacyjnego i sekularyzacyjnego paradygmatu? - Nowotarski, Bartłomiej (Demogratic Islam. The end of Paradigms of Modernization and Secularism?, 2008)
The aim of this article is to enforce the argument for democratic Islam. Recent history of so-called third wave democracies by Samuel Huntington and following waves which just embraced Middle and Eastem Europę as well as Central Asian countries undoubtedly proves that these neodemocracies are different entities - also in terms of scientific approach - in comparison with western democracies. This new category means democracies in consolidation at the beginning of the twentieth century. The article tries to weaken the modemization and neomodemization theory accordirig to which only western culture can ensure the democratic end. However, the rational choice theory has been considered as the best explanation of successful democratic transition in neodemocracies for over twenty years. The article also tries to discuss and to abolish one of the basie arguments of modemization theory relating to religion, mainly Islam. Among others, the aim of the article is to undermine the paradigm of secularism as an important aspect of modemization approach. The next step of the paper is to un- cover that the most of so-called Islamie States are - to be honest - the military-bureaucratic regimes in which muslims usually are in jails. The real breakthrough of the contemporary history is Turkey where the interpretation of Islam (ijtihad) makes morę open the Islamie jurisprudence and sharia as such. This means the core of real Renaissance of Islam. The article also recommends several topics of foreign policy of the West relating to the Islamie Republic of Iran.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 26, s. 53-77